DETERMINATION THE DEGREE OF CRYSTALLINITY OF THE POLYMERIC FILMS WITH THE HELP OF ALPHA SPECTROMETER - Abildayev, A.Kh.; Yermaganbetova, S.D. (Хабаршы. Физика сериясы, 2018)
The connection between the parameters of alpha particle energetic distribution passed through thin polymeric film, and parameters describing the crystallinity of two phase film model has been found. The procedure of determining the crystallinity degree of the thin polymeric films has been proposed, considering the film as a two phase formation i.e. mixture of crystallic and defect states.